Pembanterasan komunis di tanah Melayu - Ho, Hui Ling (Kuala Lumpur : Penerbit Universiti Malaya, 2010)
History of fighting Communism in Malaysia during the Malayan Emergency, 1948-1960
Includes bibliographical references (p. [229]-250) and index
In Malay
Keywords: Communism -- Malaysia -- History; Malaya -- History -- Malayan Emergency, 1948-1960